Measuring job openings: Evidence from Swedish plant level data - Niels-Jakob Harbo Hansen (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
In modern macroeconomic models job openings are a key component. Thus, when taking these models to the data we need an empirical counterpart to the theoretical concept of job openings. To achieve this, the literature relies on job vacancies measured either in survey or register data. Insofar as this concept captures the concept of job openings well we should see a tight relationship between vacancies and subsequent hires on the micro level. To investigate this, I analyze a new data set of Swedish hires and job vacancies on the plant level covering the period 2001-2012. I find that vacancies contain little power in predicting hires above (i) whether the number of vacancies is positive and (ii) plant size. Building on this, I propose an alternative measure of job openings in the economy. This measure has the features of (i) better predicting hiring at the plant level and (ii) providing a better fitting aggregate matching function vis-à-vis the traditional vacancy measure.
Keywords: J20; 330; Job opening; vacancies; labour supply